2005
DOI: 10.1002/ajmg.a.30970
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss in children and adults with Williams syndrome

Abstract: Williams syndrome (WS) is a genetic neurodevelopmental disorder, most often accompanied by mild-to-moderate mental retardation. Individuals with WS show unique communication strengths and impairments that are challenging to treat in community, educational, and vocational settings. Many issues regarding characteristics of auditory sensitivity in WS remain to be resolved. Our purpose was to obtain behavioral (screening and pure-tone audiometry) and objective (distortion product otoacoustic emission-DPOAE) measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
48
0
10

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 42 publications
13
48
0
10
Order By: Relevance
“…In older patients, mild to moderate high-frequency sensorineural hearing loss is described [Marler et al, 2005;Gothelf et al, 2006]. In our cohort 61% presented with hypoacusia with onset after 18 years of life, again demonstrating the importance of regular evaluations at this age.…”
Section: Discussionsupporting
confidence: 56%
“…In older patients, mild to moderate high-frequency sensorineural hearing loss is described [Marler et al, 2005;Gothelf et al, 2006]. In our cohort 61% presented with hypoacusia with onset after 18 years of life, again demonstrating the importance of regular evaluations at this age.…”
Section: Discussionsupporting
confidence: 56%
“…Neurological problems include coordination diYculties (for example, trouble walking down a staircase), hyperreXexia, cerebellar dysfunction such as ataxia and dysmetria (Chapman et al 1996;Cherniske et al 2004), strabismus (esotropia) (Kapp et al 1995;Winter et al 1996), nystagmus, hypersensitivity to sound, and sensorineural hearing loss (Marler et al 2005). The hypotonia noted in young children typically improves in childhood (Chapman et al 1996).…”
Section: Neurological Problemsmentioning
confidence: 99%
“…12 Several studies have shown that WBS patients of all ages show increased rates of mild to moderate high-frequency sensorineural hearing loss (SNHL). [13][14][15] SNHL in WBS has been shown to be progressive and the prevalence may develop to~80% of subjects over time. 16 Although many younger WBS patients seem to have hearing in the normal range, it is generally agreed that analysis of otoacoustic emissions from the cochlea of these patients indicates high rates of abnormalities, [15][16][17][18] suggesting a degree of 'cochlear fragility', 15 associated with altered sound transduction.…”
Section: Introductionmentioning
confidence: 99%